2009
DOI: 10.4103/0378-6323.57742
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lesions in Turkish neonates born in a teaching hospital

Abstract: We found that 90.7% of the neonates had one or more cutaneous lesions. Maturity and type of delivery of the babies were important factors in their causation. In Turkey, this study is the first study performed on the skin lesions seen during the neonatal period. With this study, we want to increase the awareness about the skin findings in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
45
4
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 0 publications
18
45
4
5
Order By: Relevance
“…7 In our study, congenital melanocytic nevus, black to brown flat was found in 5%. This correlates well with the incidence of a study done by Dash et al and Gokdemir et al 4,6 Melanocytic nevus involving the trunk and back were seen. The prevalence of congenital melanocytic nevi (CMN) among newborns ranges between 0.2 and 6% in the worldwide literature.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…7 In our study, congenital melanocytic nevus, black to brown flat was found in 5%. This correlates well with the incidence of a study done by Dash et al and Gokdemir et al 4,6 Melanocytic nevus involving the trunk and back were seen. The prevalence of congenital melanocytic nevi (CMN) among newborns ranges between 0.2 and 6% in the worldwide literature.…”
Section: Discussionsupporting
confidence: 76%
“…5 Most common dermatoses were noted was Mongolian spots about 20% of neonates. A similar incidence is seen in a study done by Gokdemir et al 6 However the incidence of Mongolian spots in our study is quite low in comparison with other study observed in 60.2% by 89% by Dash et al & Sachdeva et al . 4,7 The colour varies from light blue to bluish green.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…KANE A. and FERHABAS A. noted in Senegal and Turkey that desquamation + xerosis was the most frequent dermatosis [6] [10] as we observed (33.75%) at rates of 41%, 43% and 39.5% respectively. These results are in the range of 72% to 83% reported in the literature [11] [12]. In our study, miliary sweat was the second (22.29%) NND H. Adegbidi et al most encountered as in Nigerian newborns (24.6%) [8].…”
Section: Discussionsupporting
confidence: 69%
“…Bu nedenle yenidoğanın dermatolojik muayenesi ve dermatozlarının ayırıcı tanısı çok önemlidir. [1][2][3][4] . Renk Değişiklikleri: Doğum sonrası bebeğin derisi morumsu kırmızı renktedir.…”
Section: Gi Riflunclassified